The genus Orobanche L. (Orobanchaceae) in the Małopolska Upland (S Poland): distribution, habitat, host preferences, and taxonomic problems - Piwowarczyk, Renata (Biodiversity: Research and Conservation, 2012)
The paper presents the distribution of Orobanche species (parasitic herbs known as broomrapes) in the Małopolska Upland (Wyoyna Małopolska) in southern Poland. During floristic research conducted there in 1999-2011, 12 species of this genus were recorded: O. alba, O.alsatica, O .arenaria, O.bartlingii, O .caryophyllacea, O. coerulescens, O. elatior s.str., O. kochii, O. lutea, O. pallidiflora, O. picridis and O.ramosa. Eight species were not previously known from this area. Information on the hosts, abundance, and habitat preferences at the localities is given, and an updated map of the distribution in the Małopolska Upland is included. The taxonomic position of O. elatior s.str. and O.k ochii, diagnostic features to differentiate between them, and a revised map of distribution of both species in Poland are also presented.